2021
DOI: 10.3168/jds.2020-18998
|View full text |Cite
|
Sign up to set email alerts
|

Late-gestation heat stress abatement in dairy heifers promotes thermoregulation and improves productivity

Abstract: Multiparous, nonlactating pregnant cows are negatively affected by heat stress, but the effect of heat stress on more thermotolerant pregnant heifers has received less attention. Our objective was to characterize the effect of late-gestation heat abatement on thermoregulatory responses and subsequent milk production of nulliparous Holstein heifers. Pregnant heifers, blocked by body condition score (BCS) and predicted transmitting ability (PTA) for milk, were enrolled in either heat stress (HT, shade of freesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Additionally, Tao et al (2012) reported that in utero heatstressed (IUHT) calves had decreased passive immune transfer and cellular immune function as well as reduced plasma total protein and hematocrit (HCT) compared with in utero cooled (IUCL) calves. It was recently established that nulliparous, pregnant heifers are also negatively affected by heat stress, as evidenced by elevated thermoregulatory responses and reduced milk production in their first lactation (Davidson et al, 2021). Notably, the magnitude of differences in the thermoregulatory responses and production variables between cooled and heat-stressed pregnant heifers was not as large as observed differences in multiparous lactating or dry pregnant cows.…”
Section: Short Communication Physiologymentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, Tao et al (2012) reported that in utero heatstressed (IUHT) calves had decreased passive immune transfer and cellular immune function as well as reduced plasma total protein and hematocrit (HCT) compared with in utero cooled (IUCL) calves. It was recently established that nulliparous, pregnant heifers are also negatively affected by heat stress, as evidenced by elevated thermoregulatory responses and reduced milk production in their first lactation (Davidson et al, 2021). Notably, the magnitude of differences in the thermoregulatory responses and production variables between cooled and heat-stressed pregnant heifers was not as large as observed differences in multiparous lactating or dry pregnant cows.…”
Section: Short Communication Physiologymentioning
confidence: 97%
“…All heifers were housed in the same sand-bedded freestall barn, where the HT pens were provided only with shade of the open-sided barn and the CL pens were provided with shade of the barn, water soakers over the feed line, and fans over the stalls. Details on maternal treatments, thermoregulatory measures, and diets were previously reported by Davidson et al (2021).…”
Section: Short Communication Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional ( Brandão et al, 2016 ; Leiva et al, 2017 ), genetic, and management ( West, 2003 ) strategies have been reported to improve DMI, milk production and composition, health, metabolism, and reproductive function of dairy cows, or in other words, have demonstrated how heat stress might impair these productive and reproductive parameters in dairy cows ( West, 2003 ; García-Ispierto et al, 2007 ; Roth, 2008 ; Van Os, 2019 ; Bai et al, 2020 ; Pereira et al, 2021 ). Moreover, it is well-known that heat stress occurrence in pregnant dairy cows and heifers impacts gestation length ( Tao et al, 2012 ; Monteiro et al, 2014 ; Davidson et al, 2021a ) and impacts fetal intrauterine development ( Tao et al, 2012 ; Monteiro et al, 2014 ; Dado-Senn et al, 2020 ), early after birth ( Strong et al, 2015 ; Davidson et al, 2021a ), but even more importantly, later in the dairy female’s productive life ( Laporta et al, 2017 ; Tao et al, 2019 ; Davidson et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of heat stress (HS) during late gestation on the mature multiparous cow with severe consequences for several physiological mechanisms and behavioral traits in the following lactation are well known (e.g., [1,2]). Despite their suggested higher heat tolerance when compared to multiparous dry cows, quite similar HS effects during late gestation on production traits were detected for nulliparous heifers [3]. Due to the lower metabolic heat production, dry cows respond less sensitive to HS than lactating dairy cows.…”
Section: Introductionmentioning
confidence: 90%